2018
DOI: 10.12688/f1000research.13396.2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a yeast malate dehydrogenase 2 (Mdh2) antibody tested for use in western blots

Abstract: Malate dehydrogenases (Mdhs) reversibly convert malate to oxaloacetate and serve as important enzymes in several metabolic pathways. In the yeast Saccharomyces cerevisiae there are three Mdh isozymes, localized to different compartments in the cell. In order to identify specifically the Mdh2 isozyme, GenScript USA produced three different antibodies that we further tested by western blot. All three antibodies recognized the S. cerevisiae Mdh2 with different background and specificity properties. One of the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…To ensure that the peroxisomal localization of Mdh2, and its dependence on Mdh3 and Pex5, was not a result of the GFP tagging, we used a specific antibody that recognizes Mdh2 but not the other Mdh isoforms ( Gabay-Maskit et al, 2018 ). Analysis of subcellular fractions clearly demonstrated that native and untagged Mdh2 also co-sediments with peroxisomes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure that the peroxisomal localization of Mdh2, and its dependence on Mdh3 and Pex5, was not a result of the GFP tagging, we used a specific antibody that recognizes Mdh2 but not the other Mdh isoforms ( Gabay-Maskit et al, 2018 ). Analysis of subcellular fractions clearly demonstrated that native and untagged Mdh2 also co-sediments with peroxisomes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…and anti-Por1 (1:10,000; Kerssen et al, 2006 ). The Mdh2 antibody was produced by GeneScript, USA, using a specific Mdh2 peptide as an immunogen (MPHSVTPSIEQDSLC), and was previously verified by us for specificity and activity (1:2500; Gabay-Maskit et al, 2018 ). The immunodecorated membranes were incubated with IRDye 800CW goat anti-rabbit IgG or IRDye 800CW goat anti-mouse IgG (LI-COR Bioscience) as secondary antibodies, and detected with an Odyssey Infrared imaging system (LI-COR Bioscience).…”
Section: Methodsmentioning
confidence: 99%